Struggling with social-ecological mismatches in marine management and conservation at Easter Island. (June 2018) - Aburto, Jaime A.; Gaymer, Carlos F.
Abstract: In Easter Island, most of fisheries regulations are top-down implemented by the central fisheries authority located ~4000 km eastwards. This could generate problems in regulations compliance, given the cultural differences between the western worldview and Polynesian culture of Easter Island. A total of 18 issues that must be considered previously to an intervention in the island were identified. Four of them scored the highest difference between Rapanui and public services representatives. Among them, "Integrating traditions and culture" had a little priority for the public services representatives, but was the most important for the Rapanui. According to the public services representatives in Easter Island and local fishermen, there is a little compliance with regulations related to fisheries and, due to cultural aspects, it is not possible to enforce regulations and apply sanctions. The low compliance with fisheries regulations is due to the lack of representativeness of regulations. Interventions in the island are based on western worldview that does not fit with social and ecological domains of social-ecological system. A flexible governance system, based on decision making at local level in line with local tradition is needed to navigate to a resource management and conservation in Easter Island. Highlights: Easter Island and continental Chile have strong differences in their social-ecological systems. There is a lack of fit between the social-ecological systems of Easter Island and Chile. The knowledge of public services representatives about the Rapanui culture is poor. Rapanui perceive that government does interventions in a way different from what they expect. Rapanui do not comply with fisheries regulations because they do not represent their culture.